Adhesion of Pancreatic Cancer Cells in a Liver-Microvasculature Mimicking Coculture Correlates with Their Propensity to Form Liver-Specific Metastasis In Vivo. (11th May 2014) - Chowdhury, Mohammad Mahfuz; Danoy, Mathieu; Rahman, Farhana; Shinohara, Marie; Kaneda, Shohei; Shiba, Kiyotaka; Fujita, Naoya; Fujii, Teruo; Sakai, Yasuyuki
Abstract : Organ-specific characteristic of endothelial cells (ECs) is crucial for specific adhesion of cancer cells to ECs, which is a key factor in the formation of organ-specific metastasis. In this study, we developed a coculture of TMNK-1 (immortalized liver sinusoidal ECs) with 10T1/2 (resembling hepatic stellate cells) to augment organ-specific characteristic of TMNK-1 and investigated adhesion of two pancreatic cancer cells (MIA-PaCa-2 and BxPC-3) in the culture. MIA-PaCa-2 and BxPC-3 adhesion in TMNK-1+10T1/2 coating culture (TMNK-1 monolayer over 10T1/2 layer on collagen coated surface) were similar. However, in TMNK-1+10T1/2 gel (coculture on collagen gel surface), MIA-PaCa-2 adhesion was significantly higher than BxPC-3, which was congruent with the reported higher propensity of MIA-PaCa-2 than BxPC-3 to form liver metastasis in vivo . Notably, as compared to BxPC-3, MIA-PaCa-2 adhesion was lower and similar in TMNK-1 only culture on the collagen coated and gel surfaces, respectively. Investigation of the adhesion in the representative human umbilical vein ECs (HUVECs) cultures and upon blocking of surface molecules of ECs revealed that MIA-PaCa-2 adhesion was strongly dependent on the organ-specific upregulated characteristics of TMNK-1 in TMNK-1+10T1/2 gel culture. Therefore, the developed coculture would be a potential assay for screening novel drugs to inhibit the liver-microvasculature specific adhesion of cancer cells.